Agile manufacturing and transformational capabilities for sustainable business performance: a dynamic capabilities perspective - Mohaghegh, Matin; Åhlström, Pär; Blasi, Silvia (Production planning & control, 2024)
Drawing on the 'dynamic capabilities' perspective, this study empirically investigates whether, or not, and how agile manufacturing contributes to sustainable business performance, including economic, environmental, and social performance. Building on the notion that dynamic capabilities indirectly improve organisational performance through modifying a firm's resources/processes, we argue that agile manufacturing treated as a dynamic capability requires transformation to result in sustainable business performance. Therefore, we hypothesise the mediating effects of two transformational capabilities, namely internal learning, and reconfiguration capabilities, on the agile manufacturing-sustainable business performance relationship. Partial least square structural equation modelling (PLS-SEM) was employed to explore the validity of the conceptual model and examine the hypotheses using survey data from 99 Italian manufacturers firms. The results show that internal learning fully mediates the relationship between agile manufacturing and economic performance and partially mediates the relationship between agile manufacturing and social performance. Also, the empirical findings indicate that reconfiguration fully mediates the relationship between agile manufacturing and economic/environmental performance and partially mediates the agile manufacturing-social performance relationship. Overall, both transformational capabilities are necessary to maximise the effects of agile manufacturing on sustainable performance.